Analysis of Needs for the Development of Audiobooks Based on Realistic Mathematics Education for Fourth-Grade Elementary School Students - Arissona Dia Indah Sari; Tatang Herman; Wahyu Sopandi; Al Jupri; Nataria Wahyuning Subayani (Al Ibtida: Jurnal Pendidikan Guru MI, 2023)
AbstractThe purpose of this study was to describe the need for the development of an Realistic Mathematics Education (RME)-based audiobook for fourth-grade elementary school students. This study focused on two aspects, namely (1) the interest of fourth-grade students in learning mathematics; and (2) the need of RME-based audiobook media by fourth-grade teachers. The participants of this study were 135 students and 12 teachers of grade IV at four elementary schools in the Merauke area, Indonesia. Using a qualitative methodology, the data were collected through questionnaires, interviews, and documentation. The results of the study revealed that the interest of fourth-grade students in learning mathematics was still lacking. The teacher's way of teaching was considered unattractive and the mathematics learning materials delivered by the teacher were difficult to understand. Meanwhile, the need of RME-based audiobook media by the fourth-grade students and teachers was quite urgent. It was because 79% of the teachers had never used audiobook media when teaching mathematics. In addition, 53.7% of the teachers had never taught mathematics using the RME approach.Keywords: development, audiobooks, realistic mathematics education.AbstrakTujuan dari penelitian ini adalah untuk mendeskripsikan kebutuhan pengembangan audiobook berbasis RME untuk siswa kelas IV SD. Penelitian ini difokuskan pada dua aspek, yaitu (1) minat siswa kelas IV dalam pembelajaran matematika; dan (2) kebutuhan media audiobook berbasis RME oleh guru kelas IV. Partisipan penelitian ini adalah 135 siswa dan 12 guru kelas IV di empat sekolah dasar di wilayah Merauke, Indonesia. Menggunakan metode kualitatif, data dikumpulkan melalui kuesioner, wawancara, dan dokumentasi. Hasil penelitian mengungkapkan bahwa minat siswa kelas IV dalam pembelajaran matematika masih kurang. Cara mengajar guru dinilai kurang menarik dan materi pembelajaran matematika yang disampaikan guru sulit dipahami. Sementara itu, kebutuhan media audiobook berbasis RME oleh siswa dan guru kelas IV cukup mendesak. Hal ini dikarenakan 79% guru belum pernah menggunakan media audiobook saat mengajar matematika. Selain itu, 53,7% guru belum pernah mengajar matematika dengan pendekatan RME.Kata kunci: pengembangan, buku audio, pendidikan matematika realistik.